Frequency reconfigurable antenna for future wireless communication system - Rahim, M. K. A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Frequency reconfigurable antennas gain interest especially in future wireless communication systems due to flexibility in many applications. This paper reviews three different configurations of frequency reconfigurable antenna. The first configuration is the narrowband to narrowband frequency reconfigurable using slot type of antenna and microstrip antenna. The second configuration is the wideband to narrowband frequency reconfigurable antenna, planar monopole contribute to the wideband characteristic while a slot antenna is for narrowband. The third configuration used tunable electromagnetic band-gap (EBG) to configure the band notched frequency. The designed structures simulated performances and analysis are discussed in this paper. The analysis is also focused on the performance of the diode as a switch to reconfigure the frequencies.